COLONIAL ACTIVITIES OF ASSYRIAN MERCHANTS IN ANATOLIA - Arslantaş, Yüksel; Miğal, Serdar (Hamza ALTIN, 2024)
The states, which pursued land and economic interests beyond their borders, tried to reach their goals with different methods. One of these systems is commercial colonialism, which is far from oppression and violence, by controlling the raw material resources and economic activities of other countries. Nations, which wanted to expand their sovereignty and become more influential by increasing their material quality, sought colonies in which economic interests were prioritized. The Assyrians, who are among these states, turned their aim of making profit, which they started with trade, into colonialism in Anatolia, which embraced countless nations. By applying this policy, the Assyrians filled the gap that emerged with the effect of the political, social, pyschological and economic situation of Anatolia. In other words, it has shaped the socio-economic structure of Anatolia, which was economically colonized without being under political domination. The aim of working in this direction is to Express that states do not only take control of nations that do not have enough power as a result of wars and from colonies, but also keep economic relations at the forefront and fallow an expansionist policy by using activities to seize economic resources. In other words, it is to reveal that Anatolian lands were exploited by Assyrian traders outside of the usual understanding of protection. In the study, the approaches of the Assyrian merchants to the raw materical resources in Anatolia and the process of creating colonialism in the commercial relations with the local people and the gentlemen were evaluated from a critical point of view.

Kendi sınırlarının ötesinde toprak ve ekonomik çıkar peşinde koşan devletler, farklı yöntemlerle amaçlarına ulaşmaya çalışmıştır. Bu sistemlerden birisi de baskı ve şiddetten uzak, başka ülkelerin hammadde kaynaklarını, ekonomik etkinliklerini kontrol ederek yapılan ticari sömürgeciliktir. Egemenlik alanını genişletmek, maddi niteliğini arttırarak daha nüfuzlu bir hale ulaşmak isteyen uluslar, ekonomik çıkarlarını ön planda tutarak sömürge arayışı içerisine girmiştir. Bu devletlerarasında yer alan Asurlular, sayısız ulusları bağrına basan Anadolu’da, ticaret ile başladığı kâr elde etme amacını sömürgeciliğe dönüştürmüştür. Asurlular, bu politikayı uygulayarak Anadolu’nun siyasi, sosyal, psikolojik ve ekonomik durumunun etkisiyle ortaya çıkan boşluğu doldurmuştur. Yani siyasi bir egemenlik altına alınmadan, ekonomik olarak sömürge haline getirilen Anadolu’nun sosyoekonomik yapısına yön vermiştir. Bu yönde çalışmanın amacı, devletlerin yalnızca savaşlar sonucunda yeterli güce sahip olmayan milletleri kontrol alına alıp sömürgeler oluşturmadığını, ekonomik ilişkileri ön planda tutup, iktisadi kaynaklara el koyma faaliyetlerini de kullanarak yayılmacı bir politika izlediğini ifade etmektir. Yani Anadolu topraklarının Asurlu tüccarlar tarafından alışılagelmiş himaye anlayışı dışında sömürüldüğünü ortaya koymaktır. Çalışmada Asurlu tüccarların Anadolu’da bulunan hammadde kaynaklarına yaklaşımları, yerli halk ve beyler ile olan ticari ilişkilerinin sömürgeciliği meydana getirme süreci eleştirel bir bakış açısıyla değerlendirilmiştir.
ASURLU TÜCCARLARIN ANADOLU’DAKİ SÖMÜRGE FAALİYETLERİ
Keywords: Old Anatolian History; Eski Anadolu Tarihi